Radiographic referral in mandibular fracture assessment: A survey on oral maxillofacial surgeons - Murugaiah, Suganya; Oscandar, Fahmi; Azhari, Azhari (Universitas Padjadjaran, 2015)
Introduction: Epidemiological studies show a significant increase in mandibular fractures in the past few decades. Various radiographic projections are indicated for the diagnosis of mandibular fractures. This study was aimed to gather information on the type of radiographic examination commonly prescribed in the diagnosis of mandibular fracture among the oral maxillofacial surgeons and factors influencing the choice of radiographic prescription. Methods: A descriptive study with survey method was conducted on 30 respondents in the Oral Surgery Departments of three hospitals in Bandung, by purposive sampling technique. The data collected using the self-structured questionnaire method and assessed according to frequency distribution. Results: Highest choice of radiographic prescription in the survey for each location of fractures in the mandible was panoramic (83.3 to 100%), and the least is CBCT (10 to 16.7%). The most factors influencing the choice of prescription were availability (53.3 to 56.7%), image accuracy (50 to 60%) and cost (46.7 to 56.7%) of the radiographic examination. Conclusion: Most of the dentists in this study prescribe panoramic radiographs in mandibular fracture assessment based on availability, image accuracy, and cost of the radiographic examination.